ANALISIS PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN USAHATANI PENANGKARAN BENIH PADI DI KABUPATEN PESAWARAN - Yolanda Tara Mita; Dwi Haryono; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The study aims to analyse farming income, income difference between rice farming and rice seed farming, and factors that affect farmers in applying rice seed production. This study uses  a survey method and respondents are 36 rice farmers and 19 rice breeders of Tunas Baru and Mekarti Jaya farmer groups. Results showed that cost, income, and Revenue Cost(R/C) ratio of rice farming are Rp11,280,754.67, Rp14,60,.487.00, and 2.29 respectively. Meanwhile, those of rice breeding are Rp 10,373,681.80, Rp 24,822,949.77, and 3.39 respectively. Based on the independent sample of t-test, there is the difference of farming income of Rp10,220,462.77. The external factors that encourage farmers to apply rice seed production  are the price and higher income. The internal factors are the products, number of family dependents, yield, and land size, with 95 per cent of validity.Key words: income, rice seed production